1971
DOI: 10.1139/v71-498
|View full text |Cite
|
Sign up to set email alerts
|

Reductions with Sulfurated Borohydrides. VI. The Reduction of Nitro, Nitrile, Amide, and Nitroso Groups

Abstract: Aromatic nitro compounds can be reduced with sulfurated sodium borohydride to the corresponding amine in high yields ( Z 80%) without affecting ester, nitrile, ether, halide or olefinic groups also present. With ortho-substituted nitro compounds the yields are around 60%.Primary aliphatic nitro compounds are reduced to the corresponding nitrile in high yields. Secondary aliphatic nitro compounds are reduced to mixtures of ketones and the corresponding oxime. Tertiary aliphatic nitro compounds are not reduced.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1971
1971
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…This new type of hydride has shown distinctive reducing properties with aldehydes (2), ketones (3), oximes (4), nitro compounds, and nitriles (5). This paper completes this study and describes the reaction of different epoxides with NaBH,S,.…”
mentioning
confidence: 62%
“…This new type of hydride has shown distinctive reducing properties with aldehydes (2), ketones (3), oximes (4), nitro compounds, and nitriles (5). This paper completes this study and describes the reaction of different epoxides with NaBH,S,.…”
mentioning
confidence: 62%
“…9-O-(4-Aminophenyloxycarbonyl)quinine was prepared by reducing 9-O-(4-nitrophenyloxycarbonyl)quinine hydrochloride using sulfurated sodium borohydride (NaBH 2 S 3 ) [36] and a modified method of the procedure in the literature [37]. To a suspension of 2.6 g of NaBH 2 S 3 (19.7 mmol) in 100 mL of tetrahydrofuran being refluxed, 10.0 g of 9-O-(4-nitrophenyloxycarbonyl)quinine hydrochloride (19.0 mmol) in 100 mL of THF was added dropwise and allowed to react for 24 h. The reaction mixture was evaporated to dryness and the residual solid was hydrolyzed with 10% hydrochloric acid solution until pH 1 in the presence of 250 mL of diethyl ether.…”
Section: -O-(4-aminophenyloxycarbonyl)quininementioning
confidence: 99%
“…It was found that NaBH2S3 is a mild reducing agent which often shows an intermediate reducing potential between lithium aluminum hydride (LiA1H4) and sodium borohydride (NaBH4), and often gives sulfurated products of great interest. Moreover, the reducing potential of NaBH2S3 was found to be occasionally even more selective than that of LiA1H4 allowing, for example, the reduction of the nitro group in the presence of esters (3).…”
mentioning
confidence: 97%
“…In previous papers we have reported the use of sulfurated sodium borohydride (1) for the reduction of some nitrogen compounds (2)(3)(4). It was found that NaBH2S3 is a mild reducing agent which often shows an intermediate reducing potential between lithium aluminum hydride (LiA1H4) and sodium borohydride (NaBH4), and often gives sulfurated products of great interest.…”
mentioning
confidence: 99%